Linkages between financial development, financial instability, financial liberalisation and economic growth in Africa - Enowbi Batuo; Kupukile Mlambo; Simplice Asongu (African Governance and Development Institute (AGDI), 2017)
In the aftermath of the 2008 global financial crisis, the implications of financial liberalisation for stability and economic growth has come under increased scrutiny. One strand of literature posits a positive relationship between financial liberalisation and economic growth and development. However, others emphasise the link between financial liberalisation is intrinsically associated with financial instability which may be harmful to economic growth and development. This study assesses linkages between financial instability, financial liberalisation, financial development and economic growth in 41 African countries for the period 1985-2010. The results suggest that financial development and financial liberalisation have positive effects on financial instability. The findings also reveal that economic growth reduces financial instability and the magnitude of reduction is higher in the pre-liberalisation period compared to post-liberalisation period.
Keywords: O16; O47; G23; O55; 330; Economic Growth; Financial Development; Financial instability and Africa